Study of Food Recommendations to Meet Nutritional Needs Based on Diversity of Ideal Weight Calculation Methods - Ardina Anggie Christantie (Fakultas Teknik Universitas Bhayangkara, 2018)
At present, Indonesia faces multiple nutritional problems, namely the problem of malnutrition and overnutrition problems. Diet is the most influential thing in the state of individual nutrition. Nutrition that is notoptimal will be related to poor health. Nutritional problems in essence are public health problems, but theresponse cannot be done with medical approaches and health services alone. The purpose of this study is toconduct an in-depth analysis to determine the nutritional needs of each individual. The level of nutritionaladequacy and ideal body weight will be analyzed using the formula of Ideal Body Weight (BBI), Broca'sformula, and the formula for Body Mass Index (BMI). Daily calorie requirements will be analyzed using theEnergy Basal Metabolism (EMB) formula based on BMI, Harris Bennedict formula, and Perkeni formula.Recommendations for nutritional intake will be calculated using a formulation determined by the Ministry ofHealth of the Republic of Indonesia. The results of the analysis obtained from this study are the calculation ofnutritional status, ideal body weight, daily caloric needs, and recommendations for nutritional intake which refersto the nutritional adequacy standards of the Indonesian Ministry of Health and also recommends the amount offood to be consumed by individuals daily calories adjusted to the criteria of each individual, namely Normal (notsick), coronary heart sufferers, and people with Diabetes Mellitus.